Idiopathic pleuroparenchymal fibroelastosis confirmed by pathology: a case report - Cao, Min (J Int Med Res, 2021)
The case of a patient with cough and asthma after activity that each had a 1-month duration is reported. Chest high-resolution computed tomography (HRCT) showed visceral pleural thickening in both upper lungs (especially the right lung), which was accompanied by fibrous strips and patches near the pleura, and these were accompanied by distraction bronchiectasis. Idiopathic pleuropulmonary elastosis was confirmed by thoracoscopic lung biopsy. The patient was treated with acetylcysteine, but their asthma worsened after activity and their lung function decreased significantly after 10 months. Idiopathic pleuroparenehymal fibroelastosis is a rare new type of idiopathic interstitial pneumonia, which has no effective treatment except for lung transplantation.